Proton Pump Inhibitors and Risk of Acute and Chronic Kidney Disease: A Retrospective Cohort Study. Issue 4 (21st March 2019) - Hart, Emily; Dunn, Terry E.; Feuerstein, Steven; Jacobs, David M.
Abstract : Background: Proton pump inhibitors (PPIs) have been linked to acute kidney injury (AKI) and chronic kidney disease (CKD); however, current evidence has only been evaluated in a small number of studies with short follow‐up periods. This study examined the association between PPI use and risk of incident AKI and CKD in a large population‐based health maintenance organization (HMO) cohort. Methods: Patients aged 18 years or older, without evidence of preexisting renal disease, started on PPI therapy, and those continuously enrolled for at least 12 months between July 1993 and September 2008 were identified in an HMO database. Incidences of AKI and CKD were defined using documented International Classification of Disease, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes or a glomerular filtration rate less than 60 ml/min/1.73 m 2 after initiation of PPI therapy. Patients with AKI were followed for up to 90 days (cohort 1), and patients with CKD required at least 1 year of follow‐up (cohort 2). Multivariable logistic regression analyses were used to adjust for differences in demographics (excluding race), comorbidities, and medication use between groups. Results: In 93, 335 patients in the AKI cohort, 16, 593 of whom were exposed to PPIs, the incidence rate of AKI was higher in the PPI group than nonusers (36.4 vs 3.54 per 1000 person‐years, p<0.0001, respectively). In adjusted models, PPI exposure was associated with an increased risk of AKI (adjusted odds ratio [aOR] 4.35, 95% confidence interval [CI] 3.14–6.04, p<0.0001). In 84, 600 patients in the CKD cohort, 14, 514 of whom were exposed to PPIs, the incidence rate of CKD was higher in the PPI group than nonusers (34.3 vs 8.75 per 1000 person‐years, p<0.0001, respectively). In adjusted models, PPIs were associated with a higher risk of CKD compared with controls (aOR 1.20, 95% CI 1.12–1.28, p<0.0001). Associations between PPI use and AKI and CKD persisted in propensity score‐matched analyses. Conclusion: The use of PPIs is associated with an increased risk of incident AKI and CKD. This relationship could have a considerable public health impact; therefore, health care provider education and deprescribing initiatives will be necessary to raise awareness and reduce health care burden.